Morphisms of Ball's Structures of Groups and Graphs - Protasov, I.V. (Український математичний журнал, 2002)
We introduce and study two kinds of morphisms between ball's structures related to groups and graphs. Введено і досліджено два типи морфізмів між кульовими структурами, пов'язаними з групами та графами.